Nanoparticles in the Environment and Nanotoxicology (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on research concerning various types of nanoparticles in terms of their toxicity, removal of antibiotics, and behavior in natural environments. In addition, reviews on microplastics in the atmosphere and the possible health impacts of microplastics/nanoplastics on humans are included